Mindfull Meditation Sebagai Media Relaksasi Bagi Masalah Mental Emosional Pada Remaja di Kota Pekalongan - Martani, Rahajeng Win; Nahdliyyah, Ade Irma; Saarah, Siti; Firdaus, Mohammad Adnan (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2025)
Background: Adolescence is a developmental period characterized by emotional instability and vulnerability to mental health problems such as anxiety, stress, and low self-esteem. The increasing prevalence of emotional and mental issues among adolescents in Pekalongan City highlights the need for effective and accessible relaxation interventions. Methods: This community service program aimed to introduce and implement mindful meditation as a relaxation medium to help adolescents manage emotional and mental problems. The activity was carried out at SMP Negeri 13 Pekalongan through health education, guided meditation sessions, and reflection activities involving 23 students. Results: Evaluation results showed an increase in participants’ understanding of mindfulness and their ability to practice relaxation independently. Participants also reported reduced emotional tension and improved mood after regular meditation sessions. Conclusion: The findings suggest that mindful meditation can serve as a simple, low-cost, and effective strategy to promote emotional well-being among adolescents. Further programs are recommended to integrate mindfulness-based practices into school health promotion activities